2016
DOI: 10.1177/1751143716638370
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the barriers of reporting nursing errors in intensive care units: A qualitative study

Abstract: Aim: The aim of this study was to explore the barriers to reporting nursing errors in intensive care units in Iranian hospitals. Methods: A descriptive qualitative analysis design was used. The data were collected through in-depth semi-structured interviews with a purposive sample of 16 nurses working in four general intensive care units in Kurdistan province, Iran. Interviews were transcribed and finally analysed through conventional content analysis. Results: There are four major barriers to the reporting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 32 publications
6
39
0
3
Order By: Relevance
“…Given that a high perception of PSC and LCB increases nurse intention to report error it seems that hospital managers and nursing administrators have an important role to play in that they have the power to shape the working environment such that barriers to error reporting are removed and nurses are supported for doing so. Given that the greatest contributor to low levels of PSC relates to "non-punitive response errors" and the fact that a fear of punishment has consistently been found to reduce the frequency of error reporting [62], it is incumbent on health decision makers to adopt programs that create an atmosphere in which individuals can openly discuss medical errors and potential hazards.…”
Section: Resultsmentioning
confidence: 99%
“…Given that a high perception of PSC and LCB increases nurse intention to report error it seems that hospital managers and nursing administrators have an important role to play in that they have the power to shape the working environment such that barriers to error reporting are removed and nurses are supported for doing so. Given that the greatest contributor to low levels of PSC relates to "non-punitive response errors" and the fact that a fear of punishment has consistently been found to reduce the frequency of error reporting [62], it is incumbent on health decision makers to adopt programs that create an atmosphere in which individuals can openly discuss medical errors and potential hazards.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the results of Zabuli et al (2015) showed that studied nurses believed that trying to have moral performance is futile, and they were not trying to work ethically (55). Peyravi et al 2016 resulted that there were four major barriers to the reporting of errors by Iranian critical care nurses, including (1) saving professional reputation and preventing stigma, (2) fear of consequences, punishment, and legal problems, (3) feelings of insecurity and lack of managerial support and (4) not investigating the root cause of error (56).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, nurses experience difficulty in reporting 1. Reasons for under-reporting by healthcare professionals can include fear of retribution or consequences, feelings of insecurity, a belief that someone else will act or that nothing will change and protecting professional reputation 2 3. Recognising the extent of the problem and understanding factors that contribute to difficulties in reporting misconduct in home-care is essential to protect vulnerable people in care.…”
Section: Contextmentioning
confidence: 99%